It seems to me that the difficulty of this question lies not so much
in seeing the truth of the argument as in correctly applying the
mechanics of proof by induction. In what follows, I shall number an
arbitrary set of propositions from 1 to n in the following manner:
p[1], p[2], ..., p[n-1], p[n]. I use brackets in lieu of subscript
notation, so you should pronounce p[n] as "p subscript n".
Introduction
-------------
We shall prove by induction that
p[1] V p[2] V ... V p[n-1] V p[n]
p[1] -> q[1]
p[2] -> q[2]
.
.
.
p[n-1] -> q[n-1]
p[n] -> q[n]
---------------------------------
q[1] V q[2] V ... V q[n-1] V q[n]
is true for all n >= 1.
Base Case
---------
From the premises
p[1]
p[1] -> q[1]
we immediately conclude that
q[1].
Inductive Hypothesis
--------------------
We shall assume that
p[1] V p[2] V ... V p[k-2] V p[k-1]
p[1] -> q[1]
p[2] -> q[2]
.
.
.
p[k-2] -> q[k-2]
p[k-1] -> q[k-1]
-----------------------------------
q[1] V q[2] V ... V q[k-2] V q[k-1]
is true for all k greater than 1.
Inductive Step
---------------
Consider the premises
p[1] V p[2] V ... V p[k-2] V p[k-1] V p[k]
p[1] -> q[1]
p[2] -> q[2]
.
.
.
p[k-2] -> q[k-2]
p[k-1] -> q[k-1]
p[k] -> q[k].
We know from the first clause that at least one of
p[1], p[2], ..., p[k-1], p[k]
must be true.
Suppose that p[k] is true. It follows from the clause
p[k] -> q[k]
that
q[k].
On the other hand, suppose that p[k] is false.
But then one of
p[1], p[2], ..., p[k-1]
must be true, so we have
p[1] V p[2] V ... V p[k-2] V p[k-1].
But this, together with the premises
p[1] -> q[1]
p[2] -> q[2]
.
.
.
p[k-2] -> q[k-2]
p[k-1] -> q[k-1]
implies, by the inductive hypothesis, that
q[1] V q[2] V ... V q[k-2] V q[k-1].
Thus, whether p[k] is true or false, we have
q[k] V (q[1] V q[2] V ... V q[k-2] V q[k-1])
which, by the commutative and associative laws, is just
q[1] V q[2] V ... V q[k-2] V q[k-1] V q[k].
Conclusion
----------
Since the base case is true (n = 1), and the inductive hypothesis (n =
k-1) implies the inductive step (n = k) for all k > 1 (n >= 1), we
conclude that
p[1] V p[2] V ... V p[n-1] V p[n]
p[1] -> q[1]
p[2] -> q[2]
.
.
.
p[n-1] -> q[n-1]
p[n] -> q[n]
---------------------------------
q[1] V q[2] V ... V q[n-1] V q[n]
is true for all n >= 1.
If you find my answer incomplete or inaccurate in any way, please let
me know so that I have a chance to meet your needs before you assign a
rating.
Regards,
leapinglizard |